Efficacy of Opioid-Free Anesthesia with Dexmedetomidine in Inhibiting Nociception during Laparoscopic Abdominal Procedures: A Randomized Clinical Trial - Anisa Olata; Susilo Chandra; Arif H. M. Marsaban; Aida Rosita Tantri (Bali Journal of Anesthesiology)
Background: Opioid anesthesia (OA) effectively suppresses surgical stress but has significant limitations, leading to the exploration of opioid-free anesthesia (OFA) with dexmedetomidine to avoid opioid-related side effects. This study aimed to assess the efficacy of OFA with dexmedetomidine in controlling intraoperative nociception during laparoscopic abdominal surgery. Materials and Methods: A total of 58 subjects undergoing abdominal laparoscopic surgery were enrolled in the study and were randomly assigned into two groups: the OFA group (n = 29) received a dexmedetomidine bolus of 1 µg/kg, and the OA group (n = 29) received a fentanyl bolus of 2 µg/kg. Both groups received standard balanced anesthesia. Hemodynamic instability events (hypotension, bradycardia, hypertension, and tachycardia), intraoperative fentanyl rescue requirement, ephedrine consumption, and 1-h postoperative pain numeric rating scale (NRS) were documented and analyzed. Results: The two groups showed significant differences in intraoperative rescue fentanyl requirement (2 vs. 29, P < 0.001) with the amount of fentanyl dosages (50 vs 150 µg, P = 0.004), the median post-intubation qNox value (44.1 ± 5.4 vs. 49 ± 9.8, P = 0.002), and NRS scale 1 h post-surgery (1 vs. 2, P = 0.001). There was no significant difference in the number of incidences of intraoperative hypotension, hypertension, bradycardia, and tachycardia incidence between the two groups. Conclusion: OFA with dexmedetomidine is more effective than OA in inhibiting intraoperative nociception during laparoscopic abdominal surgery as it reduces the rescue fentanyl requirement while providing stable intraoperative hemodynamics.